Moderating effect of temperaments between borderline personality traits and mood instability among a sample of Lebanese adults - Emmanuelle Awad; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Souheil Hallit; Feten Fekih-Romdhane; Sahar Obeid (PLoS ONE, 2026)
Objective The aim of this study is to explore the moderating role of different affective temperaments in the relationship between Borderline Personality traits (BPT) and Mood Instability (MI) among a sample of Lebanese adults. Methods This cross-sectional study was conducted in Lebanon in May 2025. An online survey that included the Mood Instability Questionnaire – Trait Short Form (MIQ-T-SF), Temperament Evaluation of Memphis, Pisa, Paris, and San Diego – Modified (TEMPS-M), and McLean Screening Questionnaire for Borderline Personality Disorder (MSI-BPD) was used to collect data. Results A total of 872 participants completed the survey, with 66.9% being females and a mean age of 26.97 years. The interactions between borderline personality traits and depressive/cyclothymic/hyperthymic/anxious temperaments were associated with increased mood instability. Higher borderline personality scores were associated with lower (Beta = −0.50; p < 0.001) and higher (Beta = 0.39; p = 0.016) mood instability scores at low and high levels of depressive temperament respectively. Higher borderline personality scores were associated with lower mood instability scores (Beta = −0.51; p < 0.001) at low levels of cyclothymic temperament respectively. At moderate (Beta = 0.67; p < 0.001) and high (Beta = 1.41; p < 0.001) levels of hyperthymic temperament, higher borderline personality scores were associated with higher mood instability scores. Higher borderline personality scores were associated with lower (Beta = −0.37; p = 0.008) and higher (Beta = 0.40; p = 0.012) mood instability scores at low and high levels of anxious temperament respectively. The irritable temperament did not moderate the relationship between borderline personality traits and mood instability. Conclusion This study emphasizes the nature of the relationship between affective temperaments, BPT, and MI. These findings are especially important for the Lebanese population, threatened by a rising psychopathology prevalence.